Endoscopic Treatment of Boerhaave Syndrome: A Case Report - Mustafa Salih Akın; Mehmet Sait Buğdacı; Esin Korkut (Southern Clinics of Istanbul Eurasia, 2018)
Boerhaave syndrome is a spontaneous perforation of the esophagus. It is associated with high morbidity and mortality. Boerhaave syndrome is a rare condition and there are limited evidence-based guidelines for management. Endoscopic methods have become more effective over time and in many cases reduced the need for surgery, as well as reducing morbidity and mortality. Endoscopic clips are increasingly used for procedures such as polypectomy, endoscopic submucosal dissection, or natural orifice transluminal endoscopic surgery for emergencies such as bleeding or perforation. Presently described is a case of Boerhaave Syndrome treated endoscopically.